2020
DOI: 10.1002/adts.202000158
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectric Poling of Functionally Graded Ferroelectric Materials

Abstract: Flexoelectricity is a phenomenon that can yield an electromechanical coupling in all dielectric materials, whereas piezoelectricity presents itself in specially treated (electrically poled) ferroelectric materials. The present study explores the possibility of achieving electrical poling in a material, purely by mechanical means, by virtue of flexoelectricity and thereby harnessing the potential of coexistence of the two phenomena. A theoretical investigation on a functionally graded ferroelectric material sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Here the FGM system with a regular shaped (square) geometry is considered for analysis because it exhibits a more prominent flexoelectric effect due to the large strain gradient and can reduce the geometry dependency requirement of flexoelectricity (Sharma et al, 2021). In this paper, both flexoelectric and surface effects are considered.…”
Section: Geometrical Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here the FGM system with a regular shaped (square) geometry is considered for analysis because it exhibits a more prominent flexoelectric effect due to the large strain gradient and can reduce the geometry dependency requirement of flexoelectricity (Sharma et al, 2021). In this paper, both flexoelectric and surface effects are considered.…”
Section: Geometrical Considerationmentioning
confidence: 99%
“…Schematically, this can be expressed by the following relation: 𝑃 𝑖 ≈ d ijk Δ jk + ÎŒ ijkl dir Δ jk,l ; where ÎŒ ijkl dir and d ijk are direct flexoelectric (non-zero for all-dielectric materials) and piezoelectric constant (zero for non-piezoelectric materials), respectively (Chandratre and Sharma, 2012;Shu et al, 2019). Sharma et al (2021) reported the substantial enrichment in resultant coupling in the presence of flexoelectricity and piezoelectricity both in an electrically poled material sample. Besides the piezoelectric and flexoelectric effects, the surface effect is a size-dependent property that has a significant impact on the elastic response of structural building block elements.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] So it is essential to incorporate flexoelectricity while designing micro and nano‐level piezoelectric devices. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…IGA, capable of modeling gradients, was applied to capture flexoelectricity in many works. [ 21,44–48 ] Yvonnet et al. [ 49 ] used Argyris elements in their study, which provides C 1 continuity to the displacement field.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, cantilever-shaped energy harvesters and sensors, due to the presence of nonuniform strain in bending, have been vastly investigated in the past [22][23][24][25][26][27][28][29][30][31][32][33] Variable mechanical characteristics can result in varying strain distribution within the domain. A few studies have suggested the use of special composite materials to achieve variation in mechanical properties and thereby a strain gradient [34][35][36][37][38][39]. This method eliminates the need for special designs and dimensions of the devices to be employed, however, it requires an additional effort at manufacturing stage for compositional variation.…”
Section: Introductionmentioning
confidence: 99%